The Factors That Effect on Dispersion of Shutgun Pellets - Üner, Hüseyin Bülent; Şam, Bülent; Kurtaş, Ömer; Uysal, Cafer; Çerkezoğlu, Ali (The Bulletin of Legal Medicine, 2000)
Shotguns are the most popular, world wide weapons. There are a number of variables that affect the size of the shot pattern such as barrel length, shot size, range of fire, degree of choking and type of wadding. In this study test shots were carried out with various type of shotguns and ammunition and mainly the effect of the type of wadding on the size of shot pattern is investigated. It was determined that when the choke of the barrel increased, the size of shot pattern decreased. It was seen that when the shot size decreased, the size of shot pattern increased. Also, it was determined that when the range of fire increased, the size of shot pattern increased progressively. And finally, have been detected smaller size of shot pattern when power piston (plastic wad) was used instead of felt wad.Key words: Shotgun, wadding, pellet distribution.
Keywords: shotgun; wadding; pellet distribution